Reflections on “Building Back Better” Child and Adolescent Mental Health Care in a Low-Resource Postemergency Setting: The Case of Sierra Leone - Yoder - van den Brink, Hélène N.C. (Frontiers in Psychiatry, 2019)
Over the past three decades, Sierra Leone has experienced two major humanitarian crises: an armed conflict (1991-2002) and an Ebola virus disease outbreak (2014-2015). In addition to these country-wide crises, the capital Freetown experienced a mudslide affecting thousands of people in 2017. In response to these emergencies, donors and aid organizations showed an increased interest in supporting and implementing mental health and psychosocial support interventions. Despite these efforts, the mental health infrastructure of the country remains frail. Specifically, systemic improvements in the implementation of evidence-based mental health care for children and adolescents appear to be lacking. In this article, the Interactive Systems Framework for Dissemination and Implementation is used as a tool to analyze issues related to the development of a sustainable, contextually relevant child and adolescent mental health care delivery system. The author draws on her long-term experience as a child mental health specialist in Sierra Leone. Observations and hypotheses are tested and supplemented by formal and informal reports and national and international literature. The three Systems described by the Interactive Systems Framework are explored in the context of Sierra Leone: (1) Synthesis & Translation, (2) Support, and (3) Delivery. Interaction between the three Systems is discussed as critical to the successful dissemination and implementation of interventions. Ample attention is given to contextual factors that are believed to be paramount to the development of child and adolescent mental health care in Sierra Leone. The article concludes with a reflection on the usefulness of the Interactive Systems Framework in the dissemination and implementation of child and adolescent mental health care interventions in low-resource, post-emergency settings. It is suggested that in addition to funding and policies, the child and adolescent mental health system in Sierra Leone could benefit from the development of contextually relevant interventions, improvement of capacity building efforts and acknowledgement of the role of community-based practitioners in the delivery of services. Local mental health experts, especially those trained in child and adolescent mental health, should be empowered to work together with culturally competent expatriate professionals to improve child and adolescent mental health care in Sierra Leone.